Validation of Reference Genes for Accurate RT-qPCR Normalization in Aeluropus littoralis Under Drought, Cold, and ABA Treatments - Seyyed Hamidreza Hashemipetroudi; Ali Rezaei; Markus Kuhlmann (Agronomy, 2025)
Halophyte plants, with genes responsive to abiotic stress, are promising candidates to enhance crop stress tolerance, but reliable RT-qPCR analysis requires the precise selection of candidate reference genes (CRGs) due to their inconsistent expression across tissues and stress conditions. In this study eight CRGs of A. littoralis, AlEF1A, AlRPS3, AlGTFC, AlRPS12, AlUBQ2, AlTUB6, AlACT7, and AlGAPDH1, were analyzed to assess their stability for the normalization of RT-qPCR data under polyethylene glycol (PEG, 20% w/v for drought simulation), abscisic acid (ABA, 100 μM), and cold stress (4 °C) treatments. The result of the algorithms suggested different CRGs for different treatments or tissue types. However the comprehensive analysis indicates that AlEF1A is the most stable CRG for PEG-treated leaf tissue, but AlTUB6 is preferable for PEG-treated root tissue, while for PEG-treated leaf and root tissues, AlEF1A can be suggested. For cold-stressed leaf and/or root samples, AlRPS3 was the most stable. For ABA-treated leaf and root tissues, AlGTFC and AlEF1A were the most stable CRGs, respectively, whereas AlTUB6 was suggested for ABA-treated leaf and root tissues. Collectively, for all stresses combined (PEG, ABA, and cold), AlGTFC was the most stable CRG in leaf samples, while AlRPS3 was the most stable in root samples and combined leaf and root samples. The validation analysis indicates a statistically significant difference (p value < 0.05) between normalization with the most and least stable CRGs. This research suggests reliable tissue-specific RGs for A. littoralis under abiotic stresses that can enhances the accuracy of gene expression quantification.